Importance of Creative Thinking Technology in Pedagogy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Creative thinking helps us find unusual solutions to problems. However, we should not confuse it with critical thinking, but rather see it as complementary in solving impossible problems.This article talks about the importance of creative thinking technology in the pedagogical process.